Bridged oxide nanowire device fabrication using single step metal catalyst free thermal evaporation. Issue 19 (14th March 2018) - Coşkun, Mustafa; Ombaba, Matthew M.; Dumludağ, Fatih; Altındal, Ahmet; Islam, M. Saif
Abstract : In this study, bridge metal-oxide nanowires grown directly between two Si electrodes on SOI wafer and their electrical performance were investigated. Abstract : In this study, indium-tin-zinc-oxide (ITZO) and Zn doped In2 O3 nanowires were directly grown as bridged nanowires between two heavily doped silicon (Si) electrodes on an SOI wafer using single step vapor–solid–solid (VSS) growth method. SEM analysis showed highly dense and self aligned nanowire formation between the Si electrodes. Electrical and UV response measurements were performed in ambient condition. Current–voltage characteristics of devices exhibited both linear and non-linear behavior. This was the first demonstration of bridged ITZO and Zn-doped In2 O3 nanowires. Our results show that bridged nanowire growth technique can be a potential candidate for high performance electronic and optoelectronic devices.